The Role of Maqashid Sharia-Based Zakat Accounting in Supporting the Achievement of Sustainable Development Goals (SDGs) at BAZNAS North Sumatra - Mahyudin Mahyudin; Salisa Amini; Yenni Samri Juliati Nasution; Marliyah Marliyah (Journal of Accounting Law Communication and Technology, 2026)
This study examines the role of maqashid al-sharia–based zakat accounting in supporting the achievement of the Sustainable Development Goals (SDGs) at the National Zakat Agency of North Sumatra Province. Using a descriptive qualitative approach and an interpretive paradigm, the research explores the implementation of PSAK 109, the integration of maqashid al-sharia values, and the contribution of zakat programs to SDG targets. Data were collected through in-depth interviews, direct observations, and analysis of financial statements and program reports issued by National Zakat Agency. The findings reveal that National Zakat Agency North Sumatra has applied zakat accounting in accordance with PSAK 109 to ensure transparency and accountability, although the measurement of maqashid-oriented social impact has not yet been fully quantified. Core maqashid values such as hifz al-mal, hifz al-nafs, and hifz al-aql are reflected in the institution’s flagship programs, including Sumatera Utara Makmur, Sumatera Utara Sehat, and Sumatera Utara Cerdas, which contribute directly to SDG 1 (No Poverty), SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities). The study highlights that zakat accounting serves not only as a financial reporting mechanism but also as an instrument for promoting social and spiritual development aligned with maqashid al-sharia. Nonetheless, challenges remain in developing measurable indicators, strengthening human resource capacity in sharia-based accounting, and aligning maqashid values with SDG targets. The study recommends the development of a Maqashid–SDGs Index and enhanced competency building to strengthen the role of zakat in sustainable development. Overall, the findings reinforce the potential of zakat accounting as a model of Islamic sustainable accounting oriented toward societal welfare and long-term impact